DETERMINATION OF THE ICE SHEET SURFACE ELEVATION PROFILES ALONG THE INLAND TRACKS IN ANTARCTICA BY KINEMATIC GPS-OBSERVATIONS - D. V. Fedorov; L. Schröder; A. V. Egorov; C. Knöfel; E. V. Brovkov; A. Richter; V. V. Lukin; R. Dietrich (Лëд и снег, 2015)
Surface height profiles of the Antarctic ice sheet were derived from kinematic GPS observations on continental traverses with an accuracy of20 cm. The spectral analysis of the height profile allowed distinguishing different zones of distinct relief properties. The obtained surface height profiles were compared to ICESat satellite laser altimetry data and four different DEMs. A good agreement, within a few decimeters, is found between the in-situ observations and the altimetry data. Among the considered DEMs the model published by Bamber et al., 2009 [3] agrees best with the GPS observations. For three separate elevation zones the standard deviations of the differences of this DEM and the GPS results amount to 0.90 (above3300 melevation), 2.27 (2800–3300 m), and13.92 m(below2800 m). For the Rémy [13] and RAMPv2 [11] DEMs we obtained standard deviations of1.98 mand2.58 m(above3300 m), and4.03 mand5.67 m(2800–3300 m), respectively.